2017
DOI: 10.1097/dbp.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Plagiocephaly and Developmental Delay: A Systematic Review

Abstract: This review suggests plagiocephaly is a marker of elevated risk of developmental delays. Clinicians should closely monitor infants with plagiocephaly for this. Prompt referral to early intervention services such as physiotherapy may ameliorate motor delays and identify infants with longer term developmental needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 42 publications
1
51
0
3
Order By: Relevance
“…This study showed that plagiocephaly in babies/infants is more strongly associated with the motor skills area and less with the social area, as shown by previous studies [27]. In the first test, the infants showed a significant developmental delay in all areas, with a global development coefficient of 64.3, which was lower than two standard deviations of the norm [29].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This study showed that plagiocephaly in babies/infants is more strongly associated with the motor skills area and less with the social area, as shown by previous studies [27]. In the first test, the infants showed a significant developmental delay in all areas, with a global development coefficient of 64.3, which was lower than two standard deviations of the norm [29].…”
Section: Discussionsupporting
confidence: 77%
“…In previous studies, a significant neurodevelopmental delay was observed in children with deformational plagiocephaly, although no definitive relationship between the severity of deformation and the degree of developmental delay was found (the psychomotor development index was only affected by congenital anomalies) [41]. On the other hand, a systematic review showed a positive association between plagiocephaly and developmental delay in 13 of 19 studies, including four of five studies with a "strong" methodological quality [27]. Moreover, this delay was less frequent in studies with children more than 24 months of age, and motor skill development was the most commonly affected area, similar to the results of our study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Since the adoption of the Back to Sleep campaign in 1992 in USA, the prevalence of positional head deformity in early infancy has increased significantly, and the condition now occurs in one of every 60 live births, which have constituted a frequent issue of international concern . Infants with positional head deformity may lead to significant cosmetic and functional consequences, even to psychological consequences . Positional head deformity is caused by external pressures on the rapidly developing skull from prolonged exposure to one position.…”
mentioning
confidence: 99%